2008
DOI: 10.1177/0164027507311151
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Disadvantage and Black-White Disparities in Life-Course Health Trajectories

Abstract: In this study, the authors use longitudinal data from the Panel Study of Income Dynamics and growth curve models to examine the utility of the concept of cumulative disadvantage as an explanation for race differences in life-course health (self-rated) in the United States. The authors ask whether socioeconomic resources equally benefit the health of Blacks and Whites, or if Whites receive higher rates of return to resources across the life course. The authors find that the relationship differs depending on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
158
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(177 citation statements)
references
References 67 publications
13
158
3
Order By: Relevance
“…However, studies suggest that the health benefits of educational attainment are lower for African-Americans compared to Whites, particularly at higher levels of education. 70 Studies have also shown that at the same level of personal education and income, AfricanAmericans possess only one tenth of the wealth of white Americans and are more likely than whites to live in poorly resourced neighborhoods. 16,55 Our data from previous analyses in the BWHS showed a significant inverse association between neighborhood SES (measured as median housing value) and hypertension in the BWHS, and the association was present among women with high levels of education (≥16 years) 10 In the present study, the association of biomarkers and neighborhood SES was apparent in women at low and high levels of education, although the biomarker profile was in general more favorable in the more highly educated women.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies suggest that the health benefits of educational attainment are lower for African-Americans compared to Whites, particularly at higher levels of education. 70 Studies have also shown that at the same level of personal education and income, AfricanAmericans possess only one tenth of the wealth of white Americans and are more likely than whites to live in poorly resourced neighborhoods. 16,55 Our data from previous analyses in the BWHS showed a significant inverse association between neighborhood SES (measured as median housing value) and hypertension in the BWHS, and the association was present among women with high levels of education (≥16 years) 10 In the present study, the association of biomarkers and neighborhood SES was apparent in women at low and high levels of education, although the biomarker profile was in general more favorable in the more highly educated women.…”
Section: Discussionmentioning
confidence: 99%
“…Situated within life-course theory, cumulative inequality (Ferraro and Shippee 2009;Schafer et al 2011Schafer et al , 2013 and cumulative disadvantage (DiPrete and Eirich 2006;Shuey and Willson 2008) theories posit that capital, including health, accumulates through the mechanisms of "structure, human agency, and chance" (Willson et al 2007(Willson et al :1887. Regardless of the source of advantage, the advantaged have large initial gains that accumulate over the lifetime, resulting in positive outcomes (Elder 1998;O'Rand and Hamil-Luker 2005;Pearlin et al 2007;Shuey and Willson 2008).…”
Section: Cumulative Inequality/disadvantage Modelsmentioning
confidence: 99%
“…Regardless of the source of advantage, the advantaged have large initial gains that accumulate over the lifetime, resulting in positive outcomes (Elder 1998;O'Rand and Hamil-Luker 2005;Pearlin et al 2007;Shuey and Willson 2008). The converse is also true: those who are disadvantaged become increasingly disadvantaged.…”
Section: Cumulative Inequality/disadvantage Modelsmentioning
confidence: 99%
“…This approach emphasizes that strains and resources associated with stratified social conditions accumulate throughout the life course to produce advantages and disadvantages in wide-ranging life outcomes including socioeconomic status, the formation and quality of relationships, and mental and physical health (7)(8)(9)(10)(11)(12)(13). Indeed, stress experienced in childhood undermines health years and even decades later-a fact at the cornerstone of theoretical work on race and cumulative disadvantage across the life course (14-18).…”
mentioning
confidence: 99%
“…Indeed, research shows that losing a child, spouse, or parent is the most stressful life event people experience and one that affects them for years (4,20). That stress may be widely disruptive to life in ways that increase the likelihood of exposure to more stressful life events (e.g., residential disruption, divorce, job loss) and lead to chronic stressors (e.g., poverty, relationship strain) is well established (7)(8)(9)(10)(11). In these ways, a loss at one point in the life course can fuel cumulative disadvantage-and the weathering resulting from this disadvantage-over time (21).…”
mentioning
confidence: 99%